Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River - Tshibwabwa, Sinaseli M.; Stiassny, Melanie L.j.; Schelly, Robert C. (Zootaxa, 2006)
A new labeonine cyprinid, Labeo fulakariensis, is described from material recently collected in rapids on the lower Congo River near the mouth of the Foulakari River, a large north bank tributary, in the Republic of Congo, and from the Yelala rapids in the Democratic Republic of Congo. The new species is readily distinguished from other Congolese Labeo except L. greenii and L. reidi by the following combination of characters: plicate lips, characteristic striping of the flanks, and a dark spot on the base of the caudal peduncle. Labeo fulakariensis is distinguished from L. greenii by dorsal fin shape and snout without a deep transverse furrow or upwardly directed fleshy anterior appendage, and from L. reidi by the position of the eyes, the circumpeduncular scale count (16 vs 17 to 20 in L. reidi) and maxillary barbels hidden and smaller than in L. reidi.